The Story of Nai Talim: Fifty Years of Education at Sevagram: Book Review - Gaur, Nidhi (Voices of Teachers and Teacher Educators, 2017)
It is in the time of violence that one thinks of peace. We are living in such times when the frequency, scale and brutality of violence are unprecedented. Today, the violent incidents are not limited to certain pockets and areas of the country. They are reported from nearly every street corner. There is an entire range of violence being reported from rape to murder, domestic violence to road rage, vandalism to lynching. In the face of violence, one feels a need to revisit Mahatma Gandhi’s ideas on non-violence.